(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Fordyce’s disease, a rarely found disease of lips has been reported recently in department of Skin and VD, Gonosashthaya Somaj Vittic Medical College Hospital, Savar, Dhaka. Occasionally it may not be possible to identify the cause. The patient presented with identical features of Fordyce’s disease and lip biopsy for histopathology showed the features of Fordyce’s disease. Then patient was treated with Pimecrolimus cream and improved. Fordyce’s disease is an extremely rare disorder. So its cutaneous findings, histopathology and treatments are highlighted here. Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 148-151